PENINGKATAN AKTIVITAS DAN HASIL BELAJAR PSIKOMOTOR DENGAN METODE PROBLEM BASED LEARNING - Muhammad Nurtanto; Moh Fawaid (Universitas Sarjanawiyata Tamansiswa, 2015)
Learning process at SMK Ma’arif 2 Sleman still passive and uncontrolled, this condition affects to the student learning outcomes. The role of the teacher in the learning process needs to be improved with the right methods to make students more active and encourage student solve the problems. Problem Based Learning (PBL) is one of learning method which the characteristics capable of demanding learners actively and directly involved in the learning. The Aim of this study is want to know affect PBL method can increase the activity and psychomotor learning outcomes of students. The subjects were students of class XI SMK Ma’arif 2014/2015 academic year. Collecting data used in this research is qualitative descriptive analysis. The results showed an increase in activity of learners by 12.98% and psychomotor learning outcomes by implementing PBL increased 9.01%. The conclution using PBL method was known that activities of learners increase practical subject.